Epidemiology of burn injuries in the elderly: 5-year review of a burn care unit in a referral hospital in Mexico City - Vélez, Maria de los Angeles Mendoza; Salazar, Leidy Arias; Munguia, Mariana Montes; Quintana, Erika Barlandas; Luna Zepeda, Brenda Lorena (International Journal of Research in Medical Sciences, 2022)
Background: Burn injuries in elderly are one of the leading causes of morbidity and mortality in Mexican people over 65-year. The aim of this study was to describe the epidemiology of burn epidemiology in people over 65-years old over a 5-year period at a level II general Hospital in Mexico City. The objective of the study was to determine the incidence of burn injuries in people over 65-years in a regional Hospital in Mexico City over a 5-year period. Methods: Retrospective study; records of burn department of all adult patients who sustained burn injury between January 2017 to July 2021 were collected. Details about age, gender, and location of the injuries were recorded and analyzed. Results: From a total of 61 cases, 40 males (65.57%) and 21 females (34.43%) were affected. The two most burn places in the human body were the head and neck with 30 cases (49.18%), followed by the upper extremity in 29 cases (47.54%), 41 burns (67.21%) were due to flames, 13 (21.31%) due to scalds and 7 (11.48%) were electrical. Conclusions: Burn injuries in elderly people are a frequent cause of mortality injury in the burn care unit, representing a health issue in our country. Proper patient evaluation and treatment are essential to prevent further complications and subsequent morbidity and mortality in this population.